2015
DOI: 10.7567/jjap.54.034201
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the bistability characteristics of GaN/AlN resonant tunneling diodes for ultrafast nonvolatile memory

Abstract: The bistability characteristics of GaN/AlN resonant tunneling diodes (RTDs) grown on a sapphire substrate by metalorganic vapor phase epitaxy (MOVPE) were investigated to better understand their physical origin and explore their use in nonvolatile memories. The bistability current-voltage (I-V) characteristics of GaN/AlN RTDs, which were due to intersubband transitions and electron accumulation in the quantum well, were clearly observed over a wide temperature range between 50 and 300 K. However, the I-V chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…This induces the shift of E R1 and E R2 to higher energy and the transition from a high to low transmittivity. [ 14,15 ] Therefore, switching from the ON to OFF state (write memory operation) is realized by applying a forward bias voltage.…”
Section: Nonvolatile Memory Using Gan/aln Rtdsmentioning
confidence: 99%
See 2 more Smart Citations
“…This induces the shift of E R1 and E R2 to higher energy and the transition from a high to low transmittivity. [ 14,15 ] Therefore, switching from the ON to OFF state (write memory operation) is realized by applying a forward bias voltage.…”
Section: Nonvolatile Memory Using Gan/aln Rtdsmentioning
confidence: 99%
“…Therefore, we have studied a new nonvolatile memory using the intersubband transitions in GaN/AlN resonant tunneling diodes (RTDs). [ 14–18 ] This new memory, called resonant tunneling random‐access memory (RT‐RAM), has the potential to realize a high‐speed nonvolatile RAM operating at the picosecond time scale and to be used in the high‐speed region in normally off computing systems and the other applications, such as field‐programmable gate array and sensor network systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-barrier GaN=AlðGaÞN RTDs, being the simplest device to study resonant transport, have been under scrutiny during the past decades with moderate success [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Experiments on AlN-barrier RTDs grown on sapphire templates have shown a region of NDC under forward bias (the bottom contact layer is the reference of the applied voltage).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on AlN-barrier RTDs grown on sapphire templates have shown a region of NDC under forward bias (the bottom contact layer is the reference of the applied voltage). However, these devices present nonrepeatable current-voltage (I-V) characteristics [9][10][11][12]. It has been suggested that the high density of defects present in GaN films grown on sapphire (with a typical dislocation density of 10 9 cm −2 ) can act as electron traps, leading to selfcharging effects and preventing coherent transport of carriers.…”
Section: Introductionmentioning
confidence: 99%